2019
DOI: 10.3390/su11030673
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Financing Constraints of SMEs through Supply Chain

Abstract: Small and medium-sized enterprises play a crucial role in sustaining economic development in both developed economies and developing economies, however, many of them suffer from chronic and structural difficulties in accessing external financing. In this paper, we develop a theoretical framework to illustrate how information structures work in the strategic interactions between banks and firms in a supply chain, and why the transaction information in a supply chain may serve to reduce information asymmetry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Difficulty in accessing finance may cause SMEs to turn to inappropriate sources of finance and thus reduce their sustainability. Moreover, access to finance affects the growth and innovation of SMEs [52]. All in all, the evidence suggests that SMEs with better access to finance are better placed to sustain their performance and survive in today's competitive business environment.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty in accessing finance may cause SMEs to turn to inappropriate sources of finance and thus reduce their sustainability. Moreover, access to finance affects the growth and innovation of SMEs [52]. All in all, the evidence suggests that SMEs with better access to finance are better placed to sustain their performance and survive in today's competitive business environment.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Shepherd et al [51] showed that access to finance was important in enabling SMEs to achieve sustainable performance goals. Access to finance improves organizations' sustainability by making market entry easier, increasing entrepreneurial activities, boosting capacity for innovation and improving risk management skills [52]. Tiwari et al [53] showed that providing small businesses with loans at concessionary interest rates increased their access to finance hence boosted their performance.…”
Section: Access To Finance and Smes' Sustainabilitymentioning
confidence: 99%
“…Manville et al, (2019) found that supplier issues affect better SCM in UK aerospace SMEs. Yang et al (2019) reported financing constraints to be the major issue impacting the supply chain in SMEs. In Tanzania, Mollel (2015) found that information sharing and outsourcing negatively impacted SCM in food firms in Tanzania.…”
Section: Supply Chain Management (Scm)mentioning
confidence: 99%
“…Forkuoh et al (2015) also add that difficulty in accessing external financing results from the inability of these companies to reliably signal the ability to repay debts. Appropriate improvement in external financing for SMEs, compliant with the research results by Yang et al (2019), may bring measurable benefits for the entire supply chain and provide small and medium enterprises with long-term and sustainable development.…”
Section: The Financial Situation Of Smesmentioning
confidence: 97%